St Thomas de Cantilupe's Welsh miracles. (1st December 2019) - Bass, Ian
The purpose of this article is to provide transcriptions and translations of the twenty-seven miracles recorded in Oxford, Exeter College, MS 158 and Vatican, Biblioteca Apostolica Vaticana, Vat. Cod. Lat. 4015 relating to Wales. The miracles occurred through the invocation of St Thomas de Cantilupe, bishop of Hereford (1275–82), and were recorded by the custodians at the shrine in the north transept of Hereford Cathedral between 1287 and 1312. This article examines both the Oxford and Vatican manuscripts and their significance. The collection is useful for study of the context and aftermath of King Edward I's conquest of Wales in 1283 and the subsequent Anglo-Welsh conflicts and rebellions.